2000
DOI: 10.1159/000053297
|View full text |Cite
|
Sign up to set email alerts
|

Bone Markers and Bone Mineral Density during Growth Hormone Treatment in Children with Growth Hormone Deficiency

Abstract: Growth hormone (GH) has a positive impact on muscle mass, growth and bone formation. It is known to interact with the bone-forming unit, with well-documented increases in markers of bone formation and bone resorption within weeks of the start of GH therapy. These changes relate significantly to short-term growth rate, but it is not evident that they predict long-term response to GH therapy. The consequences of GH deficiency (GHD) and GH replacement therapy on bone mineral density (BMD) have been difficult to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This is the first study, to our knowledge, to investigate all three bone formation markers for which assays are available (PINP, BALP and osteocalcin) in children receiving GH treatment. The results from this cohort of short prepubertal children demonstrate and confirm previous studies, that these circulating bone formation markers, as analysed with a fully automated immunoassay system, increased on a short‐term basis during GH treatment. The GH‐mediated short‐term changes demonstrated for PINP, BALP and osteocalcin correlated with the growth response during GH treatment, thus reflecting the cellular response of GH.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is the first study, to our knowledge, to investigate all three bone formation markers for which assays are available (PINP, BALP and osteocalcin) in children receiving GH treatment. The results from this cohort of short prepubertal children demonstrate and confirm previous studies, that these circulating bone formation markers, as analysed with a fully automated immunoassay system, increased on a short‐term basis during GH treatment. The GH‐mediated short‐term changes demonstrated for PINP, BALP and osteocalcin correlated with the growth response during GH treatment, thus reflecting the cellular response of GH.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that bone formation and resorption markers were either low or normal at baseline prior to GH treatment in children with GH deficiency . Strong correlations have also been found between increased bone marker levels and changes in growth rate, and it has been suggested that bone markers should be assessed 3 months after the initiation of GH treatment as they may explain variations in growth response …”
Section: Discussionmentioning
confidence: 99%
“…This effect can be seen both in mice, in which GH overexpression increases BMD (Saban et al, 1996) and lit/lit GH-deficient or GHR knockout mice have poor peak BMD (Mohan et al, 2003; Sims et al, 2000; Sjögren et al, 2000), and in humans, in which childhood onset GH deficiency leads to decreased BMD and increased fracture risk in adulthood (de Boer et al, 1994; Holmes et al, 1994; Rosén et al, 1997; Simpson et al, 2002). GH supplementation in normal human subjects increases levels of serum bone formation markers (Holloway et al, 1994), and treatment of both animals and patients deficient in GH significantly increases their reduced BMD (Bouillon and Prodonova, 2000; Cowell et al, 2000; Simpson et al, 2002). Many of these effects of GH, however, are dependent upon age and growth period; GH deficiency leads to a 4-fold greater reduction in BMD during postpubertal growth than during prepubertal growth (Mohan et al, 2003), an effect which may be explained in part by the failure of GH to appropriately activate hepatic gene transcription in prepubertal rats (Choi and Waxman, 2000).…”
Section: Gh/igf Effects On Bonementioning
confidence: 99%
“…Childhood GHD, which is often diagnosed with less stringent criteria, (5–7) is also associated with impaired bone mineral accumulation and turnover, (8,9) and if uncorrected through puberty, may result in reduced peak bone mass in young adult life (10,11) . The extent to which failure to achieve adequate peak bone mass in late adolescence and early adulthood leads to an increased risk of subsequent osteoporosis and bone fracture remains unclear (12) …”
Section: Introductionmentioning
confidence: 99%